Adverse Effects Associated With the Use of Antimalarials During The COVID-19 Pandemic in a Tertiary Care Center in Mexico City - Lozano-Cruz, Oscar Arturo; Jiménez, José Víctor; Olivas-Martinez, Antonio; Ortiz-Brizuela, Edgar; Cárdenas-Fragoso, José Luis; Azamar-Llamas, Daniel; Rodríguez-Rodríguez, Sergio; Oseguera-Moguel, Jorge Carlos; Dorantes-García, Joel; Barrón-Magdaleno, Clemente; Cázares-Diazleal, Aldo C; Román-Montes, Carla Marina; et al. (Frontiers in Pharmacology, 2021)
Background: Antimalarial drugs were widely used as experimental therapies against COVID-19 in the initial stages of the pandemic. Despite randomized controlled trials demonstrating unfavorable outcomes in both efficacy and adverse effects, antimalarial drugs are still prescribed in developing countries, especially in those experiencing recurrent crises. Real-life experience and pharmacovigilance studies describing the use and side effects of antimalarials are still relevant. Objective: To describe the adverse effects associated with the use of antimalarial drugs in hospitalized patients with COVID-19 pneumonia at a reference center in Mexico City. Methods: A retrospective cohort with all adult patients hospitalized for COVID-19 pneumonia from March 13th, 2020, to May 17th, 2020. We compared the baseline characteristics and the adverse effects between the groups of patients treated with and without antimalarial drugs. The mortality analysis was performed in 491 patients who received optimal care and were not transferred to other institutions. Results: We included 626 patients from whom 38% (n =235) received an antimalarial drug. The mean age was 51.2 ± 13.6 years, and 64% were males. At baseline, compared with the group treated with antimalarials, the group that did not receive antimalarials had more dyspnea (82% versus 73%, p = 0.017) and cyanosis (5.3% versus 0.9%, p = 0.009), higher respiratory rate (median of 28 bpm versus 24 bpm, p < 0.001), and lower oxygen saturation (median of 83% versus 87%, p < 0.001). In the group treated with antimalarials, 120 patients had two EKG evaluations, from whom 12% (n = 16) prolonged their QTc from baseline in more than 50 ms, and six developed a ventricular arrhythmia. No significant differences were found for the change in the mean value of liver function tests per day between the groups. Among patients who received optimal care, the mortality was 16% (33/210) in those treated with antimalarials and 15% (41/281) in those not receiving antimalarials. Conclusions: The adverse events in patients with COVID-19 treated with antimalarials were similar to those who did not receive antimalarials at institutions with rigorous pharmacological surveillance. However, they do not improve survival in patients who receive optimal medical care.